2016
DOI: 10.1007/s10853-015-9718-1
|View full text |Cite
|
Sign up to set email alerts
|

Direct reduction of synthetic rutile using the FFC process to produce low-cost novel titanium alloys

Abstract: Typically, pure TiO 2 in pellet form has been utilised as the feedstock for the production of titanium metal via the solid state extraction FFC process. For the first time, this paper reports the use of loose synthetic rutile powder as the feedstock, along with its full characterisation at each stage of the reduction. The kinetics and mechanism of the reduction of synthetic rutile to a low oxygen titanium alloy have been studied in detail using a combination of X-ray diffraction, scanning electron microscopy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…S3a and S3b show the microstructures of the ground natural ilmenite feedstock before and after electroreduction, respectively. 66 More recently, low-cost and novel titanium alloys were produced directly from either synthetic rutile (i.e., rutile produced from ilmenite, with a transition metal element concentration of 3.7% and aluminium content below 1%), 21,67 or naturally occurring rutile ore (beach sand) 20 via the FFC-Cambridge process (see supplementary Fig. S3c and S3d).…”
Section: Towards Resources Sustainability a More Sustainable Feedstockmentioning
confidence: 99%
See 1 more Smart Citation
“…S3a and S3b show the microstructures of the ground natural ilmenite feedstock before and after electroreduction, respectively. 66 More recently, low-cost and novel titanium alloys were produced directly from either synthetic rutile (i.e., rutile produced from ilmenite, with a transition metal element concentration of 3.7% and aluminium content below 1%), 21,67 or naturally occurring rutile ore (beach sand) 20 via the FFC-Cambridge process (see supplementary Fig. S3c and S3d).…”
Section: Towards Resources Sustainability a More Sustainable Feedstockmentioning
confidence: 99%
“…S3c and S3d). 67 The obtained titanium alloy powder was spheroidised, and fabricated into a billet via hot isostatic pressing (HIP) and subjected to monotonic tensile testing. 20 The test result revealed that the ultimate tensile strength of this material is close to that of Ti-6Al-4V.…”
Section: Towards Resources Sustainability a More Sustainable Feedstockmentioning
confidence: 99%
“…However, the actual mechanism of conversion of TiO 2 to titanium metal appears to be more complex with formation of several sub-oxides of titanium and calcium titanate as intermediate reaction species 4,5) . It has been convincingly explained that the calcium metal deposited (due to the electrolysis of CaO dissolved in the CaCl 2 electrolyte), on the cathode (TiO 2 ) can reduce the oxide into metal through various intermediate titanium suboxides.…”
Section: Introductionmentioning
confidence: 99%
“…Following reduction of SR an a + b type titanium alloy is produced, without the cost of alloying additions. [7] Hence, the use of SR as a feedstock is notably cost-effective, as not only are feedstock costs reduced, but the dependency on master alloy additions further downstream is reduced or eliminated.…”
mentioning
confidence: 99%
“…SR-derived alloys have previously been consolidated to 98.6 pct density but no mechanical properties have been reported. [7] With respect to morphology, Ti-64 is angular, due to its production via HDH processing (Figure 3(c)). Table I provides details of the SR-derived titanium alloy and commercial Ti-64.…”
mentioning
confidence: 99%